Roles for Plant Mitochondrial Alternative Oxidase Under Normoxia, Hypoxia, and Reoxygenation Conditions - Jayawardhane, Jayamini; Cochrane, Devin W.; Vyas, Poorva; Bykova, Natalia V.; Vanlerberghe, Greg C.; Igamberdiev, Abir U. (Frontiers in Plant Science, 2020)
Alternative oxidase (AOX) is a non-energy conserving terminal oxidase in the plant mitochondrial electron transport chain that has a lower affinity for oxygen than does cytochrome oxidase. To investigate the role(s) of AOX under different oxygen conditions, wild-type Nicotiana tabacum plants were compared with AOX knockdown and overexpression plants under normoxia, hypoxia (near-anoxia), and during a reoxygenation period following hypoxia. Paradoxically, under all the conditions tested, the AOX amount across plant lines correlated positively with leaf energy status (ATP/ADP ratio). Under normoxia, AOX was important to maintain respiratory carbon flow, to prevent the mitochondrial generation of superoxide and nitric oxide, to control lipid peroxidation and protein S-nitrosylation, and possibly to reduce the inhibition of cytochrome oxidase by nitric oxide. Under hypoxia, AOX was again important in preventing superoxide generation and lipid peroxidation, but now contributed positively to nitric oxide amount. This may indicate an ability of AOX to generate nitric oxide under hypoxia, similar to the nitrite reductase activity of cytochrome oxidase under hypoxia. Alternatively, it may indicate that AOX activity simply reduces the amount of superoxide scavenging of nitric oxide, by reducing the availability of superoxide. The amount of inactivation of mitochondrial aconitase during hypoxia was also dependent upon AOX amount, perhaps through its effects on nitric oxide amount, and this influenced carbon flow under hypoxia. Finally, AOX was particularly important in preventing nitro-oxidative stress during the reoxygenation period, thereby contributing positively to the recovery of energy status following hypoxia. Overall, the results suggest that AOX plays a beneficial role in low oxygen metabolism, despite its lower affinity for oxygen than cytochrome oxidase.